Literature Review on Nicotine’s Role in Human Health - Scherer Gerhard; Pluym Nikola; Scherer Max (Contributions to Tobacco and Nicotine Research, 2024)
Next generation of nicotine/tobacco products (NGPs) include electronic cigarettes (ECs), heated tobacco products (HTPs), oral nicotine pouches (NPs) and smokeless tobacco (SLT) products (in particular snus). These products commonly contain nicotine and are intended to replace combustible cigarettes (CCs) and thus can be regarded as tobacco harm reduction products. To fulfill this role, it is essential that nicotine, which has well established addictive properties, is not causally related to health risks upon chronic use.